Erectile Dysfunction and Quality of Life among Diabetic Men: A Systematic Review of Quantitative Studies - Thongtang, Pulawit; Seesawang, Junjira (Nursing Science Journal of Thailand, 2020)
Purpose: To synthesize quantitative studies associated with quality of life (QoL) among diabetic men with erectile dysfunction (ED). Design: A quantitative systematic review was conducted. Searches of PubMed, CINAHL, and EBSCO were performed between January 2000 and September 2016. The main terms were “quality of life” and “erectile dysfunction.” Two authors independently assessed methodological quality using QualSyst tool. Main findings: Six quantitative studies concerned mostly with quality of life among diabetic men with ED were included in this review. All high-quality studies reported that diabetic erectile dysfunction (DED) had a negative impact on QoL, with increased severity of ED correlating with a lower QoL. The QoL for diabetic men with ED was worse than that of nondiabetic men with ED. Conclusion and recommendations: The existing high-quality scientific evidence reports that DED has negative effects on QoL, mainly in the dimensions of psychology and social relationships. Health care providers should actively assess erectile dysfunction in diabetic men in order to help alleviate the negative impact of DED on QoL. Future research should focus on a causal relationship between DED and QoL.